Proposing the DN(C)-model of material evidence for well-calibrated claims about past cultures - Grüning, David; Grüning, Lukas J. (Behavioral and brain sciences, 2025)
Stibbard-Hawkes presents a much-needed case for distinguishing between different types of evidence for cognition in past cultures. However, he does not outline an applicable approach for moving forward in making claims about the cognition of past cultures. We present an initial model for calibrating both absolute and comparative claims about past cultures' cognition and other traits.
Gesehen am 12.03.2025